2019
DOI: 10.1039/c9qi00195f
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of bifunctional aminopyridine into an NbO-type MOF for the markedly enhanced adsorption of CO2 and C2H2 over CH4

Abstract: An NbO-type MOF based on an aminopyridine-heterobifunctionalized diisophthalate linker was synthesized, displaying markedly enhanced C2H2 and CO2 adsorption over CH4 compared to its parent compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…To investigate the capturep erformance of 1 for CO 2 ,C 2 H 2 and CH 4 ,g as adsorption was further measured at room temperature. For three gases, 1 displays the most loading for C 2 H 2 but the least loading for CH 4 (Figures 3b and c). The adsorption amounts for C 2 H 2 ,C O 2 and CH 4 under 1a tm are 96.6, 74.5 and 19.5 cm 3 g À1 at 273 K, and 68.6, 44.8 and 10.8 cm 3 g À1 at 298 K, respectively.T he amount of C 2 H 2 is comparable with the most reported valuesi nM OFs (Table S3), but much higher than those of ZJNU-62 [40] and (Me 2 NH 2 ) 2 [Zn 6 (TBAPy) 2 (Ade) 4 (m 4 -O)].…”
Section: Gas Sorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the capturep erformance of 1 for CO 2 ,C 2 H 2 and CH 4 ,g as adsorption was further measured at room temperature. For three gases, 1 displays the most loading for C 2 H 2 but the least loading for CH 4 (Figures 3b and c). The adsorption amounts for C 2 H 2 ,C O 2 and CH 4 under 1a tm are 96.6, 74.5 and 19.5 cm 3 g À1 at 273 K, and 68.6, 44.8 and 10.8 cm 3 g À1 at 298 K, respectively.T he amount of C 2 H 2 is comparable with the most reported valuesi nM OFs (Table S3), but much higher than those of ZJNU-62 [40] and (Me 2 NH 2 ) 2 [Zn 6 (TBAPy) 2 (Ade) 4 (m 4 -O)].…”
Section: Gas Sorptionmentioning
confidence: 99%
“…[1,2] C 2 H 2 is produced primarily from methane( CH 4 )t hermal pyrolysis or hydrocarbon cracking, whichu sually coexists with some carbond ioxide (CO 2 )a nd CH 4 molecules. [3][4][5] This fact makes the separation of C 2 H 2 from C 2 H 2 and CO 2 or C 2 H 2 and CH 4 very importanti nC 2 H 2 industry.C urrent C 2 H 2 separation technology mainly relieso nt raditional refrigerant distillation. But for C 2 H 2 and CO 2 ,d ue to close boilingp oints (C 2 H 2 189.3 K, CO 2 194.7 K), almoste qual size (3.3 3.3 5.7 3 for C 2 H 2 and 3.2 3.3 5.4 3 for CO 2 )a nd identical linear shape, [6,7] the cost and energy consumptionof distillation method are very high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11d,40] 3e and Figure 3f, the hierarchy of adsorption selectivity did not change when the C 2 H 2 molar ratio in gas mixtures changed from 0.1 to 0.9. It is noteworthy that among the three MOF compounds, ZJNU-96 showed the highest C 2 H 2 /CH 4 and C 2 H 2 / CO 2 adsorption selectivities at 298 K and 1 atm, which is comparable to that of its parent MOF NOTT-101 (C 2 H 2 /CH 4 : 26.7), [16] but higher than those of some other reported MOFs such as BUT-70B (C 2 H 2 /CH 4 : 23.3), [41] PCM-48 (C 2 H 2 /CH 4 : 23.3), [42] UTSA-222 (C 2 H 2 /CH 4 : 19), [43] FJU-36 (C 2 H 2 /CH 4 : 17.7), [44] UPC-33 (C 2 H 2 /CH 4 : 7.78), [45] ZJNU-15 (C 2 H 2 /CO 2 : 4.4), [11b] Cu(BDC-Br) (C 2 H 2 / CO 2 : 3.9), [46] NTU-9 (C 2 H 2 /CO 2 : 3.5), [47] BSF-1 (C 2 H 2 /CO 2 : 3.3), [48] ZJNU-14 (C 2 H 2 /CO 2 : 3.42), [17b] UTSA-68 (C 2 H 2 /CO 2 : 3.4), [49] Zn 3 (ALP)(TDC) 2.5 (C 2 H 2 /CO 2 : 2.8), [50] and Co(btzip)(H 2 btzip) (C 2 H 2 / CO 2 : 2.5) [51] at the same conditions. In particular, the C 2 H 2 /CH 4 and C 2 H 2 /CO 2 adsorption selectivity of the ortho-dimethylfunctionalized MOF ZJNU-96 is 8.6 % and 8.3 % higher than the meta-dimethyl-decorated counterpart ZJNU-95.…”
Section: Resultsmentioning
confidence: 82%
“…The incorporated functionalities largely include the Lewis‐basic heteroatoms and polarized functional groups. For example, compared to their corresponding parent compounds, the isostructural analogues functionalized with NH 2 , [14] lactam, [15] and aminopyridine, [16] displayed significantly enhanced C 2 H 2 adsorption. Recently, we reported that relative to the pyridinic N atom, its N‐oxide moiety can substantially boost the C 2 H 2 uptake capacity [17] .…”
Section: Introductionmentioning
confidence: 99%